Intracellular localization, accumulation and distribution of heavy metals in plants (International Journal of Biology and Chemistry, 2015)
Heavy metals uptake, distribution and accumulation processes in plants are very important for their impact on physiological and biochemical processes and, consequently, on plant growth and development. The distribution of heavy metals in plant parts and cell organelles are discussed. There are detoxification mechanisms in cell compartments, like binding with cell wall, with organic acids in vacuoles, complexes with phytochelatins and etc. What proportion of given metal ions would be the in free form, and what – bound with organic molecules; it depends from pH of the environment and chemical properties of element. The stability of metals complexes decreases in the case of deviation pH of environment from neutral: at low pH there is a competition of protons with metal ions for binding sites in molecules, at high pH – by the reason of the competition of hydroxyl groups with ligand.